THE PICTURE AND PICTURE INSTRUCTIONAL MEDIA TO PROMOTE STUDENTS’ ACHIEVEMENT IN WRITING INSPIRATIONAL STORY - Mindaudah; Mahesi Riatul Mufeni (JEELL (Journal of English Education, Linguistics and Literature), 2025)
Writing inspirational stories could encourage students to take positive cues from the story. Regretfully, the initial research revealed that grade IX–D students lacked enthusiasm for writing inspirational stories. In order to ensure that at least 65% of the students could receive even the smallest score of 75, collaborative action research was carried out. Sixteen out of twenty-five students (68%) received a score of 75 and above on cycle 2 after the digital picture and picture were implemented, indicating that the action research was successful. The use of the internet to implement the digital picture was the reason for the action's success. More research on internet exploitation for the purpose of educational expansion should be completed in light of the common use of the internet in educational settings.